Achieving the ultimate optical resolution - Sánchez-Soto Luis L.; Hradil Zdeněk; Řeháček Jaroslav; Brecht Benjamin; Silberhorn Christine (EPJ Web of Conferences, 2022)
The accurate estimation of the separation between two signals is at the core of many modern technologies. We show new quantum-inspired schemes able to estimate that separation at the quantum limit. The method works in the spatial, temporal, and frequency domains. The question of whether the optical coherence brings any metrological advantage to mode projections is discussed.